Expression of influenza virus NS2 nonstructural protein in bacteria and localization of NS2 in infected eucaryotic cells. - Greenspan, D (1985)
The nonstructural NS2 protein of influenza A/PR/8/34 virus was efficiently expressed in bacteria, and monospecific antisera were prepared against the bacterially synthesized polypeptide. These antisera were cross-reactive among the NS2 proteins of various influenza A viruses. However, they did not react with the NS2 of influenza B/Lee/40 virus nor with other proteins of influenza A viruses such as NS1. Antisera against NS2 were used to determine that the NS2 protein is localized in the cell nucleus during influenza virus infection, as shown by immunofluorescence microscopy. Cells infected with simian virus 40 recombinants containing the influenza virus NS gene revealed that both the NS1 and NS2 proteins appeared in the nucleus, even in the absence of expression of other influenza virus-specific components.